The Impact of Formal School Entry on Children's Social Relationships with Parents, Siblings, and Friends - Katharina M. Heuser-Spura; Julia Jaekel; Dieter Wolke (MDPI AG, 2021)
The normative transition to formal schooling confronts children with social challenges but also opportunities. Longitudinal research on how school entry impacts children's family and friend-ship relationships is scarce. This study investigated social relationship qualities with parents, siblings, and friends among 1110 children (49.9% female) from the prospective, population-based Bavarian Longitudinal Study at 6 years (before school entry) and 8 years using a forced-choice card-sorting task. Multivariate analyses of variance revealed significant effects of age (i.e., school entry) on social relationship qualities with mothers (Pillai's Trace (PT) = 0.28, F(9, 1101) = 47.73, p < 0.001), fathers (PT = 0.14, F(9, 1101) = 19.47, p < 0.001), siblings (PT = 0.27, F(9, 1101) = 46.14, p < 0.001), and friends (PT = 0.21, F(9, 1101) = 32.57, p < 0.001). On average, children reported higher levels of parental comfort after school entry. Companionable qualities increased in relationships with friends, whereas sibling relationships became more conflictual from preschool to early school age. Findings provide unique insights into how social relationships develop from preschool to early school age, supporting evidence of the growing importance of friends. Conflict was predominant and increasing in sibling relationships and should be considered more in future research.